The effect of feeding Sodium Sesquicarbonate treated soyabean on the energy utilization and performance of broiler chickens - B. A., Ayanwale (Universiti Putra Malaysia Press, 2003)
A local variety of soyabean (Glycine max) seeds which were soaked in four different concentrations of sodium sesquicarbonate (0.0, 0.1, 0.5, and 1.0%) for 24 h, drained and air dried were used in formulating isocaloric and isonitrogenous diets for broilers. All the diets supported the growth of the broilers. No significant differences (P>O. 05) were observed in the average feed intake, body weight and body weight gains of the different groups of broilers in spite of the similarities in energy intake. Energy efficiency was significantly (P<0.05) poorer in broilers fed the control diet than in 1.0% sodium sesquicarbonate treated soyabean. Carcass evaluation showed that the proportions of the head, drumsticks and abdominal fat significantly (P<O. 05) increased as the concentration of sodium sesquicarbonate increased. Processing of soyabean with sodium sesquicarbonate reduced the crude protein (CP) and crude fibre (CF) contents of the seeds, Na+, Ca2+ and Mg;+ ions of the treated seeds increased as K+ ions decreased.